Improving Nurse Job Satisfaction in The Handover Process by The Documentation-Based SWITCH Handover Method - Ika Suhartanti; Anndy Prastya; Mujiadi Mujiadi (Fundamental and Management Nursing Journal)
Introduction: Implementation of the SWITCH handover method in the Operating Room has traditionally been conducted verbally, without standardized documentation. Effective handover is critical in perioperative settings, where detailed, timely, and accurate communication is essential. To address this issue, this study aimed to evaluate the effect of applying a documentation-based SWITCH handover method on nurse job satisfaction during the handover process.